High Energy and Short Pulse Lasers - Viskup, Richard (IntechOpen, 2016)
This book gives the readers an introduction to experimental and theoretical knowledge acquired by large-scale laser laboratories that are dealing with extra-high peak power and ultrashort laser pulses for research of terawatt (TW), petawatt (PW), or near-future exawatt (EW) laser interactions, for soft X-ray sources, for acceleration of particles, or for generation of hot dense thermal plasma for the laser fusion. The other part of this book is dealing with the small-scale laser laboratories that are using for its research on commercial sources of laser radiation, nanosecond (ns), picosecond (ps), or femtosecond (fs) laser pulses, either for basic research or for more advanced applications. This book is divided into six main sections dealing with short and ultrashort laser pulses, laser-produced soft X-ray sources, large-scale high-power laser systems, free-electron lasers, fiber-based sources of short optical pulse, and applications of short pulse lasers. In each chapter readers can find fascinating topics related to the high energy and/or short pulse laser technique. Individual chapters should serve the broad spectrum of readers of different expertise, layman, undergraduate and postgraduate students, scientists, and engineers, who may in this book find easily explained fundamentals as well as advanced principles of particular subjects related to these phenomena.